Hubungan Resiliensi dengan Psychological Well-Being pada Remaja dengan Orang Tua Tunggal - Novita, Erlina Maya; Satriadi, Sendi; Verasari, Dwi Gita (Neolectura, 2024)
Psychological well-being and resilience are important for teenagers who have single parents. Both of these things have some of the same goals, where both have the aim of achieving the best condition for the individual. The aim of this research is to empirically test the relationship between resilience and psychological well-being in adolescents who have single parents. This research was conducted on 80 respondents with certain criteria, namely teenagers who had a single parent for at least ? 6 months and lived in Jabodetabek. Data collection was carried out by distributing questionnaires containing the respondent's identity and the research scale. The scale used is the psychological well-being and resilience scale. The sampling technique used in this research is non-probability sampling with purposive sampling technique. The data analysis technique used to test the hypothesis in this research is the Kolmogrov-Smirnov normality test. Based on data analysis, the F value was 403.660 and the significance value was 0.001 (p <0.05). This shows that there is a very significant relationship between resilience and psychological well-being in teenagers who have single parents. The direction of the positive relationship shows that the higher the resilience, the higher the psychological well-being and vice versa, the lower the resilience, the lower the psychological well-being.